2011
DOI: 10.1103/physrevb.84.024115
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence and hysteresis effects in the pressure-temperature phase diagram of NH3BH3

Abstract: The potential hydrogen storage compound NH 3 BH 3 has three known structural phases in the temperature and pressure ranges 110-300 K and 0-1.5 GPa, respectively. We report here the boundaries between, and the ranges of stability of, these phases. The phase boundaries were located by in situ measurements of the thermal conductivity, while the actual structures in selected areas were identified by in situ Raman spectroscopy and x-ray diffraction. Below 0.6 GPa, reversible transitions involving only small hystere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Chen et al [63] reported a negative Clapeyron slope of the phase boundary above room temperature in their earlier XRD study in a multi-anvil apparatus, but their later Raman spectroscopy study using a DAC indicates that the boundary has a positive slope [69] and their previous XRD data were likely contaminated by the surrounding sample chamber materials in the solid pressure medium cell assembly. The positive Clapeyron slope above room temperature is consistent with the extrapolation from the II-III phase boundary below room temperature determined by Andersson et al [59] using in situ thermal conductivity measurements.…”
Section: Phase Transition From I To Iiisupporting
confidence: 89%
See 2 more Smart Citations
“…Chen et al [63] reported a negative Clapeyron slope of the phase boundary above room temperature in their earlier XRD study in a multi-anvil apparatus, but their later Raman spectroscopy study using a DAC indicates that the boundary has a positive slope [69] and their previous XRD data were likely contaminated by the surrounding sample chamber materials in the solid pressure medium cell assembly. The positive Clapeyron slope above room temperature is consistent with the extrapolation from the II-III phase boundary below room temperature determined by Andersson et al [59] using in situ thermal conductivity measurements.…”
Section: Phase Transition From I To Iiisupporting
confidence: 89%
“…Custelcean and Dreger [53] used mineral oil as pressure-transmitting medium in the sample chamber of the DAC, whereas no pressure medium was used in Trudel and Gilson's [54] experiment. Further studies [59,60] confirmed that this phase transition was indeed very sluggish and the two phases may coexist over a wide pressure range (from 0.5 to 2.5 GPa).…”
Section: Phase Transition From I To Iiimentioning
confidence: 78%
See 1 more Smart Citation
“…Chen et al [63] has determined the pressure-temperature phase boundary between the I4mm phase and Cmc2 1 phase as negative Clapeyron slope indicating the transformation is of endothermic, although it is not in agreement with the observation of Anderson et al [64]. Kumar et al has reported the I4mm to Cmc2 1 phase transition occurring at 1.22 GPa and Cmc2 1 to P1 (monoclinic) phase transition occurring at 8 GPa by combined X-ray, Neutron and theoretical investigation [65].…”
Section: High Pressure Studies Of Hydrogen Storage Materialsmentioning
confidence: 86%
“…Although, Anderson et al [83] did not observe this phase transition as they did not continue their experiment at higher pressure and low temperature region where this new phase is stable. Najiba et al [78] also observed phase B which is evident from the change of Raman modes.…”
Section: High Pressure Studies Of Hydrogen Storage Materialsmentioning
confidence: 94%